The role of PCBP1 in carbon ion-induced ferroptosis and inhibition of lung adenocarcinoma proliferation - Kang, Zhenchao; Fu, Zihan; Tian, Xuejiao; Geng, Yichao; Zhang, Qiuning; Liu, Yanli; Wang, Xinhua; Luo, Hongtao; Yang, Zhen (Frontiers in Public Health, 2025)
ObjectiveTo investigate the role of PCBP1 in the inhibition of lung adenocarcinoma proliferation by carbon irradiation.MethodsA549 cells were irradiated with different doses of carbon ions to observe clonal survival and detect changes in cell proliferation. Whole transcriptome sequencing and the Illumina platform were used to analyze the differentially expressed genes in A549 cells after carbon ion irradiation. The relationship between the expression levels of PCBP1, ACSL4, and ALOX15 and survival was analyzed by combining data from the UCSC database and the Kaplan–Meier Plotter public platform. Additionally, the knockdown of the poly (rC)-binding protein 1 (PCBP1) gene using siRNA techniques was employed to further investigate the relationship between the expression levels of PCBP1 and ALOX15. To investigate the relationship between ALOX15 expression and survival, we assessed changes in key indicators of ferroptosis (mitochondrial morphology, ROS, MDA, and divalent iron) in A549 cells after knocking down the PCBP1 gene using siRNA technology. Additionally, the expressions of PCBP1, ACSL4, and ALOX15 in different groups were further analyzed through RT-PCR and Western blot techniques. The differential expression of PCBP1, ACSL4, and ALOX15 in NSCLC tissues was found to correlate with clinical prognosis for survival.ResultsCarbon ions significantly inhibited the proliferation of A549 cells, and 5.16 Gy carbon ions significantly induced the expression of differentially expressed genes in these cells. Additionally, carbon ions inhibited the expression of PCBP1, which led to alterations in mitochondrial morphology in lung adenocarcinoma cells. This was associated with a significant increase in the levels of ROS, MDA, and Fe2+. Furthermore, low expression of PCBP1 promoted ferroptosis by increasing the expression of ACSL4 and ALOX15.ConclusionCarbon ions decreased the expression of PCBP1 in A549 cells, and low expression of PCBP1 inhibited tumor proliferation by promoting ferroptosis.